O ensino pelos mapas no espaço-tempo do território de Francisco Beltrão – Paraná - Biz, Ana Claudia (2022)
This thesis was developed in the Postgraduate Program in Geography, from UNIOESTE, campus of Francisco Beltrão, in the Education and Teaching of Geography line of research. It emerged from studies and research carried out within the scope of the RETLEE Research Group. The research aimed to contextualize the territorialization process of Francisco Beltrão city, in Paraná state, by cartographic records, and the possibilities to teach Geography through maps. The proposal is justified due to a problem identified among undergraduate students in Geography and confirmed during the investigation in which they did not recognize the city where they live on the map. Although this seems simple, it brings such complexity that it makes us think about the geography that is taught in schools. The methodology consisted in a case study, with procedures that were materialized through textual and cartographic data from the city, the state, and the country; with diagnosis and investigation by using questionnaires for undergraduate students in Geography at UNIOESTE; with collective meetings of research professors from UNIOESTE and teachers from the municipal education network of Francisco Beltrão; with discussion and evaluation of the maps with the participants regarding the historical-geographical contextualization of the city’s territory, which resulted in a portfolio of maps of the city, as a resource to assist in the teaching of Geography. The identification with the geographic space of the city, the place, and the territory where the students live constitutes the citizen formation and the maps help in this process. In the case of Francisco Beltrão, the study of its historical constitution was fundamental. The city has a history of 70 years, of which the first 20 were marked by land disputes that legitimized the definition of its territory. The territorial form of the city is the result of disputes in the region, from the distant issue of boundaries between the states of Santa Catarina and Paraná, then with the definition of regional territories, to the population seeking to legally settle in Francisco Beltrão’s territory and in the Southwest region of Paraná. In the case of Francisco Beltrão, the political, social, and economic interests of private and government companies, which interfered in the definition and identification of the territory, cannot be disregarded. The portfolio construction indicates the importance of using maps and for understanding the social processes that configure the space, for teaching Geography.